Energy poverty in Portugal: Combining vulnerability mapping with household interviews - Horta, Ana (2019)
Energy poverty seriously affects living conditions and health. In spite of its mild climate, Portugal has been pointed out as one of the most vulnerable countries in the European Union. Due to the multidimensionality of energy poverty, attention needs to be paid to specific factors contributing to it in different contexts. This paper contributes to a better understanding of energy poverty by providing results from a study combining the use of an energy poverty vulnerability index and mapping - based on a detailed quantitative analysis of all 3092 civil parishes -, with interviews conducted with 100 households in ten hotspots across the country. The sample of interviewees includes both rural and urban dwellers, several family types, and individuals of different ages, social and economic status, and living in different types of buildings. Results show the extent, but also variability, of vulnerability to energy poverty throughout the country. Findings also show that households may consider normal and acceptable to feel both cold and hot at home, either in winter or in summer. This can hinder the social recognition of the energy poverty problem and the need to tackle its negative consequences on the well-being and health of the population.